2015
DOI: 10.1097/inf.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Fever and Reversible Laboratory Abnormalities Associated with Prolonged Use of Piperacillin–Tazobactam in Children

Abstract: Piperacillin-tazobactam is used frequently in pediatric patients with complicated appendicitis and other intra-abdominal infections. We report 10 pediatric patients who developed a piperacillin-tazobactam-associated adverse reaction characterized by fever, rash, hematologic abnormalities and transaminitis. Physicians should be aware of this entity in patients treated with a prolonged course of piperacillin-tazobactam. Prompt identification can obviate unnecessary diagnostic testing and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…The association of other antimicrobials with vAKI that are not typically considered nephrotoxic should not be immediately discounted or speculated to have been due to underlying patient factors and pathophysiologies that were not captured in the multivariable analysis and require further study. [ 37 ] The analysis we have performed is in agreement with recent reports of piperacilln/tazobactam associations vAKI, which has only been recently identified. [ 38 , 39 ] The strength of the associations of nafcillin and clindamycin with vAKI warrant that the use of nafcillin or clindamycin with vancomycin should be investigated further.…”
Section: Resultssupporting
confidence: 90%
“…The association of other antimicrobials with vAKI that are not typically considered nephrotoxic should not be immediately discounted or speculated to have been due to underlying patient factors and pathophysiologies that were not captured in the multivariable analysis and require further study. [ 37 ] The analysis we have performed is in agreement with recent reports of piperacilln/tazobactam associations vAKI, which has only been recently identified. [ 38 , 39 ] The strength of the associations of nafcillin and clindamycin with vAKI warrant that the use of nafcillin or clindamycin with vancomycin should be investigated further.…”
Section: Resultssupporting
confidence: 90%
“…[32][33][34] Specific reports of adverse reactions associated with PT are related to prolonged use. 33 Our study showed no difference in days of intravenous antibiotics in either group. Mean days on PT was approximately 5 days, with no short-term adverse reactions or antibiotic related complications.…”
Section: Discussionmentioning
confidence: 99%
“…29 Tazocin use in children is associated with adverse reactions, characterized by fever, rash, hematologic abnormalities, and transaminitis. 30 Gentamicin is associated with nephrotoxicity and ototoxicity; therefore, drug levels have to be carefully monitored. 31,32 In the case of biliary atresia (BA) treatment, information on serious side effects of the antibiotics is missing, but reports on increasing adverse events and resistant infections in other underlying diseases are worrying.…”
Section: Discussionmentioning
confidence: 99%